Tinjauan Keakuratan Data pada Sensus Harian Rawat Inap Di Rumah Sakit Khusus Bedah Banjarmasin Siaga - Deasy Rosmala Dewi; Gussa Azizah; Retno Juwita; STIKES Husada Borneo (Jurnal Kesehatan Indonesia, 2014)
Inpatient daily census is the number of inpatient at a health care facility at any given time starting at 00:01 until 24.00 each day. In practice involving nurses and medical record officer. However, there were limited data accuracy daily inpatient census at the Hospital for Special Surgery Siaga Banjarmasin such differences initial data on patients with the remaining patients the day before. Inaccuracies in charging daily census affects the quality of information produced hospital. The purpose of this study was to determine the accuracy of the data on the daily inpatient census at the Hospital for Special Surgery Siaga Banjarmasin. This research is descriptive. As a research population is daily inpatient census VIP classes, I, II, and III in January 2013 as many as 124 sheets. The samples used in this study is saturated sampling as many as 124 sheets. Data was collected through interviews and observation. The results of 124 samples of known Standard Operating Procedures (SPO) daily inpatient census at the Hospital for Special Surgery Standby Banjarmasin still using the old procedures and there has been no revision in 2013, the implementation of the inpatient daily census there are many inaccuracies in filling the remaining number of patients a day prior to the initial patients by nurses, and the rest of the room there are many inaccuracies in the rest of the patients and 53,5% of patients beginning with the criteria quite well. Recapitulation of the inpatient daily census is 46.46% with the criteria quite well.